Complementarity-An Essay on the 40th Anniversary of the Hicks-Allen Revolution in Demand Theory - Samuelson, Paul A. (Journal of Economic Literature, 1974)
THE TIME is ripe for a fresh, modern look at the concept of complementarity. Whatever the intrinsic merits of the concept, forty years ago it helped motivate Hicks and Allen to perform their classical reconsideration of ordinal demand theory. And, as I hope to show, the last word has not yet been said on this ancient preoccupation of literary and mathematical economists. The simplest things are often the most complicated to understand fully. For this reason, I have redrafted the present paper along the following lines: The main discussion is primarily literary. Then comes a mathematical section. Finally, I give a brief survey of the history of the subject.